Acculturation, resilience, and the mental health of migrant youth: a cross-country comparative study. (September 2018) - Wu, Q.; Ge, T.; Emond, A.; Foster, K.; Gatt, J.M.; Hadfield, K.; Mason-Jones, A.J.; Reid, S.; Theron, L.; Ungar, M.; Wouldes, T.A.
Abstract: Objectives: Using data from an international collaborative research project on youth resilience in the context of migration, this study aims to investigate how different acculturation patterns (i.e. integration, assimilation, separation and marginalization) influence the mental health of migrant youth, and whether resilience might function as a mediator in the association between acculturation and mental health. Study design: A cross-sectional pilot study conducted in six countries employing a common survey questionnaire. Methods: The study sample was 194 youths aged 10–17 years (median = 13.6) from six countries (Australia, Canada, China, New Zealand, South Africa, and United Kingdom) and included cross-border and internal migrants. Mental health and well-being was measured by the Warwick–Edinburgh Mental Well-Being Scale (WEMWBS). Resilience was measured by the Child and Youth Resilience Measure-28 (CYRM-28). Acculturation was assessed using the Acculturation, Habits, and Interests Multicultural Scale for Adolescents (AHIMSA). Multivariate regression and path analysis were performed to examine the hypothesized mediation model. Results: Resilience scores correlated strongly with mental health and well-being. Acculturation exerted no significant direct effects on the mental health of migrant youths. Nevertheless, compared to youths who were integration-oriented, assimilation-oriented youths tended to exhibit lower levels of resilience, resulting in poorer mental health. Compared to youths from other countries, migrant youths from China also reported lower levels of resilience, which led to poorer mental health outcome. Conclusion: Acculturation plays a significant role in the mental health of migrant youth, with different acculturative orientations exhibiting different influences through the mediation effect of resilience. Fostering resilience and facilitating integration-oriented acculturation are recommended public health strategies for migrant youth. Highlights: Acculturation orientation is predictive of the mental health of migrant youths. Resilience functions as a mediator in the association between acculturation and youths' mental health. The country context of migration is influential for the resilience and mental health of migrant youths.